PREPARATION AND SHELF LIFE STUDIES OF EUGENIA JAMBOLANA (JAMUN) LEATHER - Fatima, Syeda K; Umar, Zahida N; Zuberi, Rabia (Biological Sciences - PJSIR, 2004)
Eugenia jambolana (Jamun) leathers were made from jamun pulp with and without jamun seeds using solar with electric drying. Comparative investigation of jamun pulp and its products were conducted in terms of moisture, total soluble solids as degree brix, pH and pectin. Shelf life of the products were monitored for more than six months. Very slight change in color, flavor and texture in two of the products during storage at 15°C was observed. The Microbiological study revealed the absence of molds and coliforms. The total bacterial counts were 5-15 Cfu/g and 15-50 Cfu/g values for initial and at the end of shelf life, respectively.